2000
DOI: 10.2351/1.521923
|View full text |Cite
|
Sign up to set email alerts
|

CO 2 and Nd:YAG laser beam welding of 6111-T4 aluminum alloy for automotive applications

Abstract: CO 2 laser beam welding of AM60 magnesium-based alloyThere are two important trends that are currently taking place in the forming of sheet metal into automotive body components. One of these trends is the substitution of aluminum sheet alloys for steel. The other trend is the use of tailor welded blanks. Currently, there exists strong motivation for research to combine these technologies in order to produce tailor welded aluminum blanks. The focus of the current study is to develop welding procedures for auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 13 publications
0
21
1
Order By: Relevance
“…Also, a 4.5 kW CO 2 laser produced penetration depths of 3.5 mm in aluminum alloy series 5000 (non heat-treatable) and 6000 (heat-treatable), at a speed of approximately 33 mm/s; in comparison, a 4 kW Nd:YAG laser produced weld depths of 4 mm at the same speed (Cao et al., 2003). In addition, Ramasamy and Albright (2000) showed that when welding with a pulsed 2 kW Nd:YAG, or a 3 kW continuous wave Nd:YAG, or a 3-5 kW CO 2 laser, vaporization of magnesium and/or silicon could occur from aluminum alloy 6111-T4 and also the metal hardness was reduced. This means that when operating at very high power densities, loss of alloying elements is a significant problem.…”
Section: Laser Welding Of Aluminum Alloysmentioning
confidence: 96%
“…Also, a 4.5 kW CO 2 laser produced penetration depths of 3.5 mm in aluminum alloy series 5000 (non heat-treatable) and 6000 (heat-treatable), at a speed of approximately 33 mm/s; in comparison, a 4 kW Nd:YAG laser produced weld depths of 4 mm at the same speed (Cao et al., 2003). In addition, Ramasamy and Albright (2000) showed that when welding with a pulsed 2 kW Nd:YAG, or a 3 kW continuous wave Nd:YAG, or a 3-5 kW CO 2 laser, vaporization of magnesium and/or silicon could occur from aluminum alloy 6111-T4 and also the metal hardness was reduced. This means that when operating at very high power densities, loss of alloying elements is a significant problem.…”
Section: Laser Welding Of Aluminum Alloysmentioning
confidence: 96%
“…The change in the chemical composition of the laser processed part is a function of the vaporisation rate and the volume of the molten pool [185,186]. Although, alloying vaporisation rate increases with the dissipated energy density, the change in composition is most pronounced at low energy density levels due to small size, and the high surface-to-volume ratio, of the molten pool [185,186]. Therefore, employing laser processing conditions combining medium or high power with high scanning rates is critical to avoiding alloying vaporisation [184].…”
Section: Loss Of Alloying Elementsmentioning
confidence: 99%
“…The presence of Mg is very important in 5000 series and 6000 series alloys; as is Zn in 7000 series alloys (Cross et al 2003). Ramasamy and Albright (2000) found that vaporisation of magnesium and silicon occurred and metal hardness was reduced in welding of aluminium alloy 6111-T4 with a 2-kW Nd:YAG laser in the pulsed mode, a 3 kW continuous wave Nd:YAG laser, or a 3-5 kW CO 2 laser.…”
Section: Other Defects In Laser Beam Weldingmentioning
confidence: 99%